P14.13 Severe hematological toxicity during chemoradiation for glioblastoma: Identification of clinical and pharmacological risk factors and consequences for the individual patient. (9th September 2021) - Grun, N; den Otter, C A; Sintemaartensdijk, M; Osinga, J; van den Elzen, F E L; van der Vegt, A N; de Haan, J; Bruynzeel, A M E; van Linde, M E; Postma, T J; Schuur, M; de Witt Hamer, P C; et al.
Abstract: BACKGROUND: Besides early tumour progression, standard first-line radiation with concurrent and adjuvant temozolomide in de novo glioblastoma patients is abrogated frequently by severe haematological toxicity. This leads to treatment delays with unknown effect on efficacy and to more hospital visits with increased disease burden. In the present study, we identified clinical and pharmacological risk factors for temozolomide induced severe hematological toxicity. Furthermore, we describe the burden of toxicity for patients and evaluate the effect of severe toxicity on prognosis. METHODS: A retrospective cohort study of adult patients with a histological confirmed glioblastoma (n=363), treated with standard treatment regimen at the Brain Tumor Center Amsterdam between 2000 and -2020. Severe haematological toxicity was defined as a CTCAE (version 5.0) grade ≥3. We used Pearson Chi-Square test to analyze differences in patient characteristics between the groups (no vs. severe toxicity) and paired samples T- Test to analyze fluctuations in cell counts. Univariate and multivariate logistic regression were used to identify patient- and treatment characteristics associated with severe hematological toxicity. Cox Proportional Hazards models were used to estimate Hazard Ratio's for the association between survival and severe hematological toxicity. RESULTS: Female gender (OR 8.05, 95%CI 2.96–21.89, p<0.001) and older age (age > 70 years; OR 2.44, 95%CI 1.12–5.31, p=0.025) were independent risk factors for severe toxicity. Concurrent and adjuvant temozolomide was discontinued in respectively 56% and 35% of the patients. In general, patients with severe hematological toxicity had a treatment delay of 22 ± 48 days. Of all patients with severe hematological toxicity during chemoradiation, 96% developed toxicity after ≥4 weeks of treatment (p<0.001). Females who received highest temozolomide-doses (4 th quartile) had a longer survival than females with low cumulative temozolomide doses (1 st quartile). Patients, who developed severe toxicity had much more hospital visits (20; range 12–26), and were admitted more frequently to the hospital. Severe haematological toxicity was not related to survival (HR 1.04; 95%CI 0.74–1.45). CONCLUSION: Female gender and age >70 years are risk factors for severe hematological toxicity. Severe hematological toxicity relates to temozolomide exposure and results in a significant treatment burden for patients. Low temozolomide exposure results in decreased survival. Patient tailored therapy may result in better treatment outcomes.